Growth Rate of Rhizophora apiculata Propaguls in Two Sylvofishery Ponds in Tanjung Rejo Village Percut Sei Tuan District - Delvian; Siahaan, Indri Marita; Rambey, Ridahati (Talenta Publisher, 2019)
Research on Growth Rate of propaguls of Rhizophora apiculata was carried out in Tanjung Rejo Village, Deli Serdang Regency, North Sumatra. The purpose of this study was to compare the growth of Rhizophora apiculata in two sylvofishery ponds. The parameters measured were height, diameter and number of leaves. During twelve weeks of observation, the height of the seedlings of Rhizophora apiculata was the best at ponds A, namely in the fifth week 1.8 cm with the best diameter increase of 0.2 cm, the highest number of leaves was 7 strands. At the ponds B, the highest increase in seedlings of Rhizophora apiculata was observed in the fifth week 1.8 cm, but did not experience any increase at all in the second week, with increasing diameters of about 0.05 - 0.1 cm, number of leaves range from 0 to 5 strands. This shows that the growth of Rhizophora apiculata is better at ponds A than at ponds B.